Single‐cell transcriptome profiling reveals molecular heterogeneity in human umbilical cord tissue and culture‐expanded mesenchymal stem cells. (11th May 2021) - Wang, Quanlei; Li, Jinlu; Wang, Shengpeng; Deng, Qiuting; Wang, Kuixing; Dai, Xi; An, Yanru; Dong, Guoyi; Ke, Weilin; Chen, Fang; Liu, Longqi; Yang, Huanming; et al.
Abstract : Human umbilical cord‐derived mesenchymal stem/stromal cells (UMSCs) demonstrate great therapeutic potential in regenerative medicine. The use of UMSCs for clinical applications requires high quantity and good quality of cells usually by in vitro expansion. However, the heterogeneity and the characteristics of cultured UMSCs and the cognate human umbilical cord tissue at single‐cell resolution remain poorly defined. In this study, we created a single‐cell transcriptome profile of human umbilical cord tissue and the cognate culture‐expanded UMSCs. Based on the inferred characteristics of cell clusters and trajectory analysis, we identified three subgroups in culture‐expanded UMSCs and putative novel transcription factors (TFs) in regulating UMSC state transition. Further, putative ligand–receptor interaction analysis demonstrated that cellular interactions most frequently occurred in epithelial‐like cells with other cell groups in umbilical cord tissue. Moreover, we dissected the transcriptomic differences of in vitro and in vivo subgroups and inferred the telomere‐related molecules and pathways that might be activated in UMSCs for cell expansion in vitro . Our study provides a comprehensive and integrative study of the transcriptomics of human umbilical cord tissue and their cognate‐cultured counterparts, which paves the way for a deeper understanding of cellular heterogeneity and offers fundamental biological insight of UMSCs‐based cell therapy. Abstract : Human umbilical cord‐derived mesenchymal stem cells (UMSCs) are a promising tool for regenerative medicine. In vitro expansion of UMSCs is required to provide a sufficient quantity and quality of cells for clinical application, but the characteristics of cultured UMSCs are poorly defined. Here, Zhouchun Shang et al . used single‐cell RNA‐seq analysis to reveal the subgroups in human umbilical cord tissue and cognate culture‐expand UMSCs, highlighting putative novel transcription factors that regulate state transition in UMSCs. They also report that epithelial‐like cells communicate with stromal cells via ligand‐receptor interactions and infer telomere‐related pathways that might be activated during in vitro UMSCs expansion.